Crotacetin, a novel snake venom C-type lectin homolog of convulxin, exhibits an unpredictable antimicrobial activity - Radis-Baptista, G.; Moreno, FBMB; Nogueira, L. D.; Martins, AMC; Toyama, D. D.; Toyama, M. H.; Cavada, B. S.; de Azevedo, W. F.; Yamane, T. (Humana Press Inc, 2006)
Snake venom (sv) C-type lectins encompass a group of hemorrhagic toxins that are capable of interfering with blood stasis. A very well-studied svC-type lectin is the heterodimeric toxin, convulxin (CVX), from the venom of South American rattlesnake Crotalus durissus terrificus. CVX is able to activate platelets and induce their aggregation by acting via p62/GPVI collagen receptor. By using polymerase chain reaction homology screening, we have cloned several cDNA precursors of CVX subunit homologs. One of them, named crotacetin (CTC) beta-subunit, predicts a polypeptide with a topology very similar to the tridimensional conformations of other subunits of CVX-like snake toxins, as determined by computational analysis. Using gel permeation and reverse-phase high-performance liquid chromatography, CTC was purified from C. durissus venoms. CTC can be isolated from the venom of several C. durissus subspecies, but its quantitative predominance is in the venom of C. durissus cascavella. Functional analysis indicates that CTC induces platelet aggregation, and, importantly, exhibits an antimicrobial activity against Gram-positive and -negative bacteria, comparable with CVX.
Keywords: Crotalus durisssus venom; snake venom C-type lectin; crotacetin; convulxin; platelet aggregation; antimicrobial activity